2022
DOI: 10.1159/000522193
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Vitamin D Levels and Vitamin D-Binding Protein Polymorphisms on Nonalcoholic Fatty Liver Disease Risk in a Chinese Population

Abstract: Introduction: Vitamin D binding protein (VDBP) is correlated with non-alcoholic fatty liver disease (NAFLD) through the biological functions of regulating plasma vitamin D (VD) level and the inflammatory process. Objective: This study aims to investigate the effects of VD level and VDBP gene polymorphisms on the risk of NAFLD in a Chinese population. Methods: Plasma 25-hydroxyvitamin D3 [25(OH)D3] levels were measured and seven VDBP candidate genetic variants (rs222020, rs2282679, rs4588, rs1155563, rs7041, rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…A total of 19 records were further excluded at this stage since they did not report the outcome of interest. Finally, a total of 12 studies fulfilled the eligibility criteria [20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 19 records were further excluded at this stage since they did not report the outcome of interest. Finally, a total of 12 studies fulfilled the eligibility criteria [20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Search Resultsmentioning
confidence: 99%
“…A total of 12 studies consisting of at least 18,012 participants combined reported the outcome of interest [20][21][22][23][24][25][26][27][28][29][30][31]. These studies were conducted in 2010 to 2022.…”
Section: Characteristics Of Studies Reporting the Association Between...mentioning
confidence: 99%
See 3 more Smart Citations